Gross‐dependent lower limb lymphoedema. Issue 2 (19th January 2017) - Hennessy, Mairead Marion; O'Brien, Gavin Connor
Key Clinical Message: Gross‐dependent lower limb lymphoedema is an unusual condition which can be painful particularly if ulceration occurs. Focused history and clinical examination in addition to appropriate radiological investigation aid in the diagnosis. It is difficult to treat and requires a multidisciplinary team including vascular surgeons, dermatologists and clinical nurse specialists. The primary treatment option is compression bandaging. Abstract : Gross‐dependent lower limb lymphoedema is an unusual condition which can be painful particularly if ulceration occurs. Focused history and clinical examination in addition to appropriate radiological investigation aid in the diagnosis. It is difficult to treat and requires a multidisciplinary team including vascular surgeons, dermatologists and clinical nurse specialists. The primary treatment option is compression bandaging.